Analisis Interaksi Obat Pada Penyakit Ginjal Tahap V (On Hemodialisa) Berdasarkan Resep Di Instalasi Farmasi Rumah Sakit Pelabuhan Jakarta Selama Januari - Juni 2013 - Diana Laila Ramatillah; Stefanus Lukas; Tri Hastuti (Jurnal Farmasi Higea, 2014)
Drug interactions are interactions that occur when a drug is altered by the effects of other drugs, food, or beverages. Drug interactions can cause a reduction in effects of therapeutic, increasing of toxicity or pharmacological activity that is not expected whereas according to its severity, it is divided into major, moderate and minor. From the results of "Analysis of Drug Interactions V-Stage Renal Failure (On Hemodyalisis) from Recipe at Instalation of Pharmacy Pelabuhan Hospital Jakarta", It can be concluded that the number of male patients more than female patients as many as 10 people. In this study the highest of comorbidity was diabetes mellitus at 35.25 % while the largest of the other disease except renal failure in 5-stage on HD was diabetes mellitus at 35.25%.  During this study, there was 165 cases and among them only 13 cases or 7.3 % experienced the interaction of drug. Most of cases were pharmacokinetic interaction which had 9 cases and the average of severity was minor at 8 cases.